MADRASAH MANAGEMENT BASED ON STOCK (CASE STUDY IN MADRASAH ALIYAH DARUL AMIEN TABUK LABAK AND MADRASAH ALIYAH ONE ROOF AL AZHAR KANDANGAN HULU SUNGAI DISTRICT SELATAN - Armiati, Armiati; H., Wahyu; Ahmad, Karyono Ibnu (Indonesian Researcher Society for Science Technology and Education (IDREST) Publisher, 2019)
Cottage based madrasas are madrassas that integrate Islamic boarding schools into madrasah subjects and management. The purpose of this study was to analyze curriculum management, management of teaching staff and education and management of students in the Aliyah Darul Amien Taluk Labak Madrasah and the One Roof Madrasah Alyah Al Azhar Kandangan District of HSS. This study uses a descriptive qualitative approach. Data collection techniques with study interviews, observations and documents. Data sources: Head of Madrasah, Deputy Head of Madrasah in the Curriculum Sector, Deputy Head of Madrasah for Student Affairs and Administration. Checking the validity of the data is done by source trigulation and trigulation methods. Based on research findings, the two madrassas have carried out curriculum management. The curriculum used is the Ministry of Education / Ministry of Religion curriculum that is collaborated with the cottage curriculum. There are few obstacles in the implementation of the curriculum, there are still teachers who do not yet understand about K13. The implementation of curriculum evaluation at Darul Aliyah Madrasa Amien Taluk Labak further showed the peculiarities of a cottage-based madrasa. In the reception of Darul Amira Taluk Labak Aliyah Madrasah employees prioritizing alumni with the reason that it is easier to be fostered, so that sometimes it is not in accordance with the required competencies, while Al Azhar Kandangan One-Roof Madrasah Aliyah sometimes has difficulty getting employees in accordance with the required competencies. Guidance and development as well as compensation for employees in Darul Amien Taluk Labak Aliyah Madrasah is good enough, while in Al Azhar Kandangan One-Stop Islamic Madrasah, employee development and development is almost never done and compensation given is still somewhat less suitable for work, for example: no there is overtime pay for overtime employees. The management of students in Darul Amien Taluk Labak Aliyah Madrasah has been very good and really shows the peculiarities of a cottage-based madrasa, while Al Azhar Kandangan One-Roof Islamic Madrasahs still lack the typical cottage-based madrasa. Suggestion: 1. Both madrassas can increase collaboration with Trustees supervisors and outsiders, to increase the competence of teachers about K13. 2. Both madrassas can open as much employee acceptance as possible to obtain competent personnel as needed. 3. One-Roof Aliyah Madrasah Al Azhar Kandangan Al-Azhar Kandangan One-Stop Islamic Madrasah can improve employee coaching, development and assessment more intensively to improve employee competency and pay more attention to compensation to encourage employees to work optimally.